The Epidemiology of Neurological Complications in Adults With Sickle Cell Disease: A Retrospective Cohort Study - Maduakor, Chinedu; Alakbarzade, Vafa; Sammaraiee, Yezen; Vakrinou, Angeliki; Corobana, Alina; Sikorska, Julia; Rhodes, Elizabeth; Pereira, Anthony C. (Frontiers in Neurology, 2021)
Introduction: Risk factors for neurological complications in sickle cell disease differ in the adult and pediatric populations. Here, we focused on neurological complications in adults with sickle cell disease. Methods: Patients were selected using the audit data from the St George's Hospital Red Cell Database. The genotyping, demographics, clinical data, and investigation findings were collected. Results: A total of 303 patients were enrolled in the study: hemoglobin S homozygosity (HbSS) genotype 56%, hemoglobin S and C coinheritance (HbSC) genotype 35%, and hemoglobin S and β-thalassemia coinheritance (HbSβ) thalassemia genotype 9%; the mean age was 38.8 years (±13.5 SD) with 46% males. The most common neurological complication was cerebrovascular disease (n = 37, 12%) including those with ischemic stroke (10%), cerebral vasculopathy (3%), and intracranial hemorrhage (1%). Ischemic stroke was common among the HbSS genotype compared with other genotypes (8 vs. 1.6%, p = 0.001). Comparing the patients with sickle cell disease who had suffered a stroke to those who had not, there was a higher proportion of intracranial vasculopathy (p = 0.001, in particular, Moyamoya) and cognitive dysfunction (p < 0.0001). Conclusion: Our cohort supports previous reports that the most common neurological complication in adult sickle cell patients is cerebrovascular disease. Strategies to prevent cerebral vasculopathy and cognitive impairment should be explored.